EFFICACY OF GROWTH PROMOTING HORMONES ON GROWTH AND YIELD OF RICE (Oryza sativa L.) - NAPHISABET NONGPHLANG; SHIKHA SINGH; DHANANJAY TIWARI,; NARREDDY HINDUJA; SUSANA BASAIAWMOIT (The Bioscan, 2021)
A field experiment during Kharif, 2019 was conducted at Crop Research Farm, Department of Agronomy, Naini Agricultural Institute, SHUATS, Prayagraj, Uttar Pradesh, to find out the effect of gibberellic acid (GA 3 ) and naphthalene acetic acid (NAA) on growth and yield of rice. The data revealed that among the treatment, RDF + 75 ppm NAA at 45 DAT recorded the highest plant height (93.63 cm) whereas, RDF + 50 ppm GA 3 at 45 DAT recorded maximum total tillers (13.20), dry matter accumulation (2945.48 g/m 2 ), effective tiller/hill (9.27), number of grains/panicles (147.33), 1000 grain weight (23.08 g), grain yield (5.47 t/ha), straw yield (11.60 t/ha), rupee unit in gross return (160533.33 t /ha), net return (110383.54 t /ha) and B:C ratio (2.21). Thus we can conclude RDF + 50 ppm GA 3 at 45 DAT is more productive and economic, which enhanced yield by 22.66 % and 29 % of net return over control.